Internet use among older Europeans: an analysis based on SHARE data - König, Ronny; Seifert, Alexander; Doh, Michael (Universal access in the information society, 2018)
Access to the Internet is becoming increasingly important for all generations. However, a digital gap in Internet use remains between younger and older individuals as well as within the elderly population itself. This study, therefore, aimed to investigate Internet use among elderly Europeans. Representative data across 17 countries from the Survey of Health, Ageing and Retirement in Europe (SHARE) were examined. Analyses were based on the responses of 61,202 Europeans aged ≥ 50. Results highlight that, on average, 49% of all respondents use the Internet. However, the situation varies widely among European countries. Alongside individual indicators, such as age, gender, and social class, results indicate that previous experience with computers during one’s time in the workplace is positively associated with Internet use in old age. Furthermore, use of the Internet among an individual’s social network positively influences their use. Wider contextual structures such as area of residence and country-specific wealth and communication technology infrastructure also tend to promote Internet use among elderly Europeans. Data from SHARE indicate that private Internet use among older Europeans is driven by personal resources, prior experiences with technology, social salience as well as contextual influences.